A study of the permanganate oxidation of trans-cinnamaldehyde - Enanoza, Rudyard M.
The permanganate oxidation of trans-cinnamaldehyde in aqueous medium has been studied form pH 1 to 7. An acid-catalyzed reaction was observed. Benzoic acid was found as the major product formic acid, oxalic acid, and CO2, minor products. A most probable route of the reaction is proposed.